(untitled) (MAUSAM, 1990)
Global velocity potential fields based on the FGGEE III data set from the ECMWF have been used to study the low frequency mode of the global circulation relevant to the Indian monsoon by performing EOF analyses. Development of monsoon in relation to the annual cycle is examined.